The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ma14195701
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Surface Roughness of Abrasive Belt Grinding of Superalloy Material Based on RLSOM-RBF

Abstract: It is difficult to accurately predict the surface roughness of belt grinding with superalloy materials due to the uneven material distribution and complex material processing. In this paper, a radial basis neural network is proposed to predict surface roughness. Firstly, the grinding system of the superalloy belt is introduced. The effects of the material removal process and grinding parameters on the surface roughness in belt grinding were analyzed. Secondly, an RBF neural network is trained by reinforcement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In the investigation of microchips generated during the lapping film finishing process, examinations were conducted directly on the abrasive tool surface after the completion of the process (see Figures 5,[6][7][8][9][10][11]. Due to the non-conductive nature of the abrasive tool surface, which is crucial for obtaining sharp images at high magnifications during electron microscope measurements, and considering that the chips are of micro and nanometric dimensions, graphs of the microchips at high magnifications (see Figures 7 and 8) were captured on the double-sided carbon tape surface.…”
Section: Research On Microchips Lapping Film Finishing Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the investigation of microchips generated during the lapping film finishing process, examinations were conducted directly on the abrasive tool surface after the completion of the process (see Figures 5,[6][7][8][9][10][11]. Due to the non-conductive nature of the abrasive tool surface, which is crucial for obtaining sharp images at high magnifications during electron microscope measurements, and considering that the chips are of micro and nanometric dimensions, graphs of the microchips at high magnifications (see Figures 7 and 8) were captured on the double-sided carbon tape surface.…”
Section: Research On Microchips Lapping Film Finishing Productsmentioning
confidence: 99%
“…After use, the worn-out film is wound onto a roller, which simultaneously serves as a driving roller. This single-use feature distinguishes this method from processes utilizing endless [5] abrasive belts [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one kind of artificial intelligence-based approach, GRNN is a special form of radial basis function neural network [ 32 , 33 , 34 , 35 , 36 ], and has been widely applied to many fields [ 37 , 38 , 39 ]. Compared with the current popular feedforward neural network, it has a number of advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Conclusions came from the resent investigations on the features of abrasive tools [3,8,19,20], process kinematics [21], the influence of the processed material properties on the process results [22][23][24][25][26] and cutting fluid [9,27]. In the assumptions for the new method, the developed methodology of process monitoring [28,29], a thorough analysis of the properties of abrasive tools [30][31][32], and the topography of the treated surfaces [33] were used. The results of the simulations described in the works [34,35] were used into account which showed that in the recent period of application of grinding processes, they even extended to the nanometric scale.…”
Section: Introductionmentioning
confidence: 99%